Analisis Keaktifan Pembelajaran Siswa pada Mata Pelajaran Akidah Akhlak di MA Sa’id Yusuf Depok - Zaeni Dahlan; Nurul Fadilah; Eva Siti Faridah; Ernawati Ernawati (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
This research was conducted based on the factor of low activity in the learning process of students and teaching teachers so that it affects various factors in learning activities, for example, motivation to learning outcomes that are less than optimal from the learning process. From the results of observations at MA Sa'id Yusuf Depok, especially in class X on the subject of moral aqidah, that there are some students who are very passive in the learning process. So the teacher must be able to create an active and interesting and fun learning atmosphere so that students are interested in being active in the learning process. The purpose of this study was to find out the description of student learning activities, and to find out what were the obstacles in developing student learning activities and what efforts were made by the institution in developing student activity, so as to know the results obtained after efforts were made in the learning process of class X students. MA Sa'id Yusuf on the subject of AkidahAkhlak. The method used is observation, researchers make observations by going directly into the classroom by paying attention and analyzing the learning process at MA Sa'id Yusuf Depok. Then the research data analysis used descriptive qualitative methods to determine the level of activeness of students and teachers and to find out what efforts should be made and get optimal results. Keywords: active learning of students, the subject of moral aqidah